Promoting Accessibility: Workshop Experiences with Design Thinking - dos Remedios, Sara Elene Lobato; Braz, Priscilla Fonseca de Abreu; Alves, Aline Da Silva; Da Silva, Marina Maria Ribeiro Gomes; Barbosa, Gabriela Silveira (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2024)
According to the most recent Brazilian census conducted by the IBGE, approximately 24% of the population has a disability, a figure that tends to increase over time. Attitudinal and communicational barriers hinder the access of people with disabilities to various services, including health services, frequently resulting in their invisibility and fostering vulnerability and inequality. In this context, this paper presents an experience report on conducting accessibility workshops using the Design Thinking approach at a public institution engaged in research, health promotion, and social development. The purpose of these workshops was to identify potential gaps and needs of this institution's employees in the implementation of accessibility measures in various communication, information, and health-related domains. The reported experience was lived in the context of a larger project that aims to systematize guidelines for more accessible practices in public policies of communication, information, and health. Involving participants with and without a disability facilitated a closer proximity of collaborators to accessibility-related aspects as well as among them.